A New Solution of Time-Fractional Coupled KdV Equation by Using Natural Decomposition Method. (1st September 2020) - Elbadri, Mohamed; Ahmed, Shams A.; Abdalla, Yahya T.; Hdidi, Walid
Abstract : In this article, we applied a new technique for solving the time-fractional coupled Korteweg-de Vries (KdV) equation. This method is a combination of the natural transform method with the Adomian decomposition method called the natural decomposition method (NDM). The solutions have been made in a convergent series form. To demonstrate the performances of the technique, two examples are provided.